The diversity of zerconid mites (Acari, Zerconidae) in Giresun province, with a new record for the Turkish fauna - Urhan, S. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2015)
The zerconid mites collected from the Giresun province between December 2009 − April 2011 are evaluated and the following species are recorded: Prozercon buraki, P. demirsoyi, P. giresunensis, P. mersinensis, P. murati, P. satapliae, P. traegardhi, P. turcicus, Zercon adoxyphes, Z. agnostus, Z. berlesei, Z. bulancakensis, Z. bulgaricus, Z. colligans, Z. denizliensis, Z. imperfectsetosus, Z. karadaghiensis, Z. mirabilis and Z. ozkani. Of these, Z. karadaghiensis is recorded for the first time from Turkey. Description and drawings of the newly recorded species are given. On the basis of the collected specimens, measurements of nineteen species are given and their geographic distributions are discussed. Additionally, altitude and habitat preferences of the zerconid species are presented with 3 figures and 4 tables.